Human Diversity in Education: An Integrative Approach - Crushner Kenneth (MC Graw Hill, 2009)
Human Diversity in Education: An Integrative Approach is a research-based, comprehensive text designed to provide an introduction to multicultural education and diversity in society. The text prepares future teachers for the wide diversity of students that they are certain to meet in their classrooms, schools, and communities. It provides an updated and broad treatment of the various forms of human diversity found in today’s schools including nationality, ethnicity, race, religion, gender, class, language, sexual orientation, and ability levels.